PROFIL DARAH AYAM BROILER SETELAH VAKSINASI AI DAN PEMBERIAN BERBAGAI KADAR VCO - Wachidah Yuniwarti, Enny Yusuf (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
This research aimed to improve number of erythrocyte and hemoglobin as an altrnative to AI disease prevention through increase chicken immunity. Erythrocyte and hemoglobinÂ  in addition to a role in oxygen distribution also plays a role in enhancing the immune system. This research used 40 one-day-old broiler chickens. The method applied was Completely Randomized Factorial Design in which the first factor was two levels of vaccine, namely groups of AI vaccinated and unvaccinated. The second factor was four levels of VCO namely 0, 5, 10, 15 mL/kg feed. Day Old Chick (DOC) were divided into eight treatment groups and repeated five times. Feed and water were given ad libitum for four weeks. The result showed that the number of erythrocyte influenced by the AI vaccination were hemoglobin levels are influenced by the AI vaccination and feeding VCO. Â  Key words: Avian influenza, chicken, VCO, erythrocyte, hemoglobin